Penetrating Cervical Trauma Following a Suicide Attempt in a Young Patient: A Case Report - Nioca, Maria; Nascimento, Dulcilene; Constantino, Anilton; de Araujo, Nelsa (Brazilian Journal of Case Reports, 2026)
A 23-year-old previously healthy male patient was admitted following a suicide attempt by strangulation using a metallic wire associated with blunt trauma to the anterior cervical region. Initial examination revealed an extensive laceration-contusion injury in zone II of the neck, with significant active bleeding and exposure of laryngotracheal structures. Surgical exploration identified a grade III laryngeal injury according to the Schaefer-Fuhrman classification, with complete mucosal exposure, as well as a grade IV tracheal injury based on the American Association for the Surgery of Trauma (AAST) classification, involving loss of more than five tracheal rings. No injuries to major cervical vessels or nerves were observed. Tracheostomy, laryngorrhaphy, and hemostasis by ligation of small vessels of the prethyroid musculature associated with electrocautery were performed. The patient remained hospitalized in the intensive care unit for five days, followed by 15 days of inpatient care, receiving multidisciplinary follow-up from general surgery, psychology, and psychiatry teams. During clinical evolution, persistent suicidal behavior was observed, requiring sedation and intensive surveillance. The patient was discharged with outpatient follow-up and antidepressant therapy. This case illustrates the severity of penetrating cervical trauma associated with suicide attempts, highlighting the importance of immediate surgical management and integrated psychiatric care, while also discussing the global and national epidemiology of suicide.